Language and Democracy in Nigeria: A Stylistic Study of Late President Umar Musa Yar’adua’s Inaugural Speech of May 29, 2007 - Murana Muniru Oladayo (Journal of Linguistics and Communication Studies, 2023)
Language is central to the activities of politics as it is employed by politicians throughout the world to gain, use, delegate and retain power. In the inauguration of a new president, a requisite component of the rites is the delivery of address marking the formal beginning of a new government. Traditionally, it is a speech marked by its persuasive and commission orientations besides its request for solidarity. This paper attempts a stylistic analysis of President Musa Yar’adua’s inaugural speech of May 29, 2007 for its peculiar appeal at the time of delivery and the trust it gained though the speaker died during his tenure of office. The analysis covers the various levels of stylistic description to establish the choices that account for the effectiveness of the address. It finds that the speech is typical in its promise of good leadership and appeal for support. It identifies the devices of style in the speech to include purposeful capitalization, sustained rhythmic flow, complex verbal group, flexible sentence types, apt lexical and syntactic choices, dislocation and vocative. The paper concludes that the unity of purpose which characterizes the address is a product of the apt choices made and its overall quality is marked by tactfulness. It thus recommends that the kind of felicitous oratorical techniques used in the speech translates to administrative ingenuity needed for salvaging Nigeria from poverty, political cabals, disease and underdevelopment by Nigerian presidents henceforth.